THE CONCEPT OF GENDER IN LANGUAGE - Наталья Базаровна Раджапова (Bright Mind Publishing, 2025)
Language is not only a means of communication, but also forms our ideas about the world, as well as reflects and reinforces existing social inequalities and stereotypes. The article examines the object and subject of this research is language as a social phenomenon, as well as its relationship with gender norms and stereotypes.
Keywords: Gender linguistics, stereotypes, language, gender neutrality, society, communication.